Storm Water Management Model Simulation and Evaluation of the Eastern urban drainage system of Cali in the face of climate variability scenarios (2019)
(Eng) Occurrence of extreme hydroclimatological events associated with climatic variability and climate change, along with deficient development of urban drainage systems, have increased the occurrence of floods in cities. This study analyzes the hydraulic behavior of the urban drainage system in the e ast of Cali, during the occurrence of maximum rainfall events, supported by the Storm Water Management Model. Three simulation climate scenarios were developed: (i) current scenario with a return time of 2 and 10 years, (ii). a climate scenario for the yea r 2030 and (iii) a climate scenario for the year 2040. The model presented an acceptable grade of calibration, with a Nash - Sutcliffe number greater than 0.5 in simulated events, therefore the results obtained appropriately describe the behavior of surface runoff in the study area, in terms of spatial and temporal resolution. In this way, critical points of the drainage system were identified. This information may be potentially useful in the planning of future hydraulic works, leading to an improvement of t he hydraulic behavior of the system, and the protection of life and property of the inhabitants of the city.